Marketing channels : - Pelton, Lou E (Irwin/McGraw-Hill, 1997)
This book is the first text to use the relationship marketing perspective in the channels course. The authors have created a Channels Relationship Model (CRM), which is the guiding framework of the book. This book will contain a combination of text, cases, and readings. It contains coverage of global and ethical issues. Careful attention is paid to the pacing of material throughout the semester